Effect of sunlight-initiated processes on dexamethasone degradation in liquid samples - Joanna Wilk; Paulina Sowik; Klaudia Stando; Adrianna Grabowska; Ewa Felis; Sylwia Bajkacz (Desalination and Water Treatment)
Dexamethasone is a widely used drug, largely excreted unmetabolized, and in this form it enters the environment posing a risk of causing hormonal imbalances in humans and animals. The effectiveness of heterogeneous photocatalysis under controlled conditions of simulated sunlight using three photocatalysts, TiO2 anatase, TiO2 Degussa P25 and ZnO, in degrading dexamethasone at a concentration of 1 mg L−1 was investigated. TiO2 Degussa P25 proved to be the most effective semiconductor, degrading 98.93 % of the compound within 10 minutes. The effect of methanol used as a solvent for dexamethasone added to the reaction mixture was also determined. In each case, it slowed down the reaction rate, compared to an aqueous solution of the standard. Five transformation products formed during irradiation of the model samples were identified. The most effective photocatalyst was used to degrade dexamethasone in environmental matrices. For river and tap water, satisfactory removal of 94.7–98.5 % of the drug was achieved within 60 minutes. Photocatalysis in municipal wastewater showed 79.3 % degradation after 120 minutes. Three transformation products were present in environmental samples after the process. Additionally, characterization of the environmental samples was performed, demonstrating that mineralization of dexamethasone during photocatalysis occurred only to a limited extent.